EFL TEACHERS’ LEVEL OF TEACHER ACTION RESEARCH ENGAGEMENT - Yunita Puspitasari (STKIP PGRI Jombang, 2022)
Teachers doing action research has been recommended as a powerful and transformative model for teacher professional development but remains trivial among the population of teachers worldwide, including those who teach English as a foreign language (EFL). The present study investigates EFL teachers’ level of engagement with and in Teacher Action Research (TAR), as well as their motives for the engagement. Employing a quantitative approach with a survey as the design, a questionnaire was distributed to EFL teachers teaching at secondary school to collect data. Descriptive statistics were run to analyze the data. The results showed that EFL teachers’ engagement with TAR was high, while their engagement in TAR was moderate. Thus, encouraging EFL Teachers to conduct TAR will consequently get them used to continuously make reflections on what they did in their classroom in which better teaching-learning quality can be achieved. Besides, the policy makers should provide some fundamental supports to encourage the teachers making the research engagement.